AN ANALYSIS ON THE MAIN CHARACTER OF A GOOD TEACHER IN “THE CLARK STORY” MOVIE - Khoirul Huda (English Language Teaching Department (Prodi Pendidikan Bahasa Inggris), 2017)
This thesis journal is concerned on an analysis on Characterization of the Main Character of Ron Clark Story movie. This study is trying research the characterization of the main character as a good teacher of Ron Clark Story movie. In this study the researcher states this study intends to analyze, (1) how are the characterizations of the main character shown as a good teacher in the movie? (2) How is the main character described as a Good Teacher in The Ron Clark Story Movie by characterization technique? This study is intended to describe: (1) to describe how the characterization of the main character as a good teacher in the movie. (2) To describe how the main character as a good English teacher that described in the “Ron Clark Story” movie by characterization technique. The researcher uses descriptive qualitative design. This research is categorized as qualitative research because the researcher presents the data by describing the data based on the characterization of Ron Clark as the main character by the characterization technique. The result of this study shows that there are 2 data for inspiring, there is 1 data for self-confidence, there are 3 data for innovative, there is 1 data for caring, there are 2 data for helpful, there are 2 data for creative, there are 2 data for humorist, there are 2 data for responsible, there is 1 data for hard worker, and there is 1 data for discipline. So, it can be concluded that characterization of Ron Clark is the main character as a good teacher who innovative, caring, humorist, responsible, hard worker, discipline.